In vitro antibacterial activities of PD 138312 and PD 140248, new fluoronaphthyridines with outstanding gram-positive potency. - Huband, M D (1993)
PD 138312 and PD 140248 are new quinolones with high in vitro activities against a wide spectrum of bacterial species, notably including gram-positive isolates. The respective MICs (in micrograms per milliliter) of PD 138312 and PD 140248 capable of inhibiting > or = 90% of the strains were < or = 0.06 and < or = 0.06 for oxacillin-susceptible and -resistant staphylococci, streptococci (including Streptococcus pyogenes, S. agalactiae, S. pneumoniae, and viridans group streptococci), Haemophilus influenzae, Moraxella catarrhalis, and Neisseria gonorrhoeae; 0.125 and 0.03 for Legionella pneumophila; 0.25 and 0.125 for Listeria monocytogenes; 0.25 and 0.25 for Enterococcus faecalis; 0.5 and 0.06 for anaerobic gram-positive cocci; 0.5 and 0.25 for Acinetobacter spp.; 0.5 and 0.5 for members of the family Enterobacteriaceae (excluding Serratia marcescens); 2 and 0.5 for Bacteroides fragilis; 2 and 2 for Serratia marcescens and ciprofloxacin-resistant staphylococci; and 8 and 4 for Pseudomonas aeruginosa.